2014
DOI: 10.1242/bio.20146445
|View full text |Cite
|
Sign up to set email alerts
|

Wild bees preferentially visitRudbeckiaflower heads with exaggerated ultraviolet absorbing floral guides

Abstract: Here, we report on the results of an experimental study that assessed the visitation frequency of wild bees to conspecific flowers with different sized floral guides. UV absorbent floral guides are ubiquitous in Angiosperms, yet surprisingly little is known about conspecific variation in these guides and very few studies have evaluated pollinator response to UV guide manipulation. This is true despite our rich understanding about learning and color preferences in bees. Historical dogma indicates that flower co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
35
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 67 publications
9
35
0
2
Order By: Relevance
“…The positive effect of UV nectar guide area on pollen receipt observed here corroborates previous studies that have reported a positive effect of UV floral guide presence, size, or proportion on pollinator visitation rate (Horth et al, ; Leonard & Papaj, ; Rae & Vamosi, ). UV bullseyes or UV nectar guides are often interpreted as guides that direct floral visitors toward a floral reward (Leonard & Papaj, ; Orban & Plowright, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The positive effect of UV nectar guide area on pollen receipt observed here corroborates previous studies that have reported a positive effect of UV floral guide presence, size, or proportion on pollinator visitation rate (Horth et al, ; Leonard & Papaj, ; Rae & Vamosi, ). UV bullseyes or UV nectar guides are often interpreted as guides that direct floral visitors toward a floral reward (Leonard & Papaj, ; Orban & Plowright, ).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown that the spatial patterns in which flowers reflect and absorb UV light specifically affect the behavior of potential pollinators. A variety of floral UV-absorption patterns (e.g., "nectar guides" or "bullseyes") may attract and guide insects, promoting efficient pollination (Horth, Campbell, & Bray, 2014;Leonard & Papaj, 2011). In addition, the size of the UV floral guide has been shown to positively influence pollinator visitation rate and pollen transfer efficiency (Horth et al, 2014;Leonard & Papaj, 2011).…”
Section: Which Floral Traits Are Attractive To Bees?mentioning
confidence: 99%
“…UV patterns on petals can be perceived by bees ( Chittka, 1992 ), birds ( Bennett and Cuthill, 1994 ), moths ( Sheehan et al., 2016 ) and flies ( Koski and Ashman, 2015a ). Furthermore, both bees and flies have been shown to prefer flowers with large UV bulls-eye patterns ( Horth et al., 2014 , Koski and Ashman, 2015a , Brock et al., 2016 ). Therefore, we predicted that natural selection would drive the evolution of flowers with larger bulls-eye patterns in C. scaposa .…”
Section: Discussionmentioning
confidence: 99%
“…For example, flowers of most species in Potentilla are yellow, but some of them show quite different UV absorption patterns ( Naruhashi and Ikeda, 1999 , Koski and Ashman, 2016 ). Despite the fact that this kind of UV absorbing floral type is generally correlated with bioclimatic factors ( Koski and Ashman, 2015b , Koski and Ashman, 2016 ), it has been suggested that flowers with larger UV absorption patterns may be perceived ( Chittka et al., 1994 , Briscoe and Chittka, 2001 , Kevan et al., 2001 , Koski and Ashman, 2014 , Sheehan et al., 2016 ) and preferred ( Horth et al., 2014 , Brock et al., 2016 ) by insects as the bulls-eye patterns are thought to act as nectar guides. Accordingly, we cannot judge pollination syndrome of a flower color based on human eyes only, and measurements of phenotypic selection on floral traits should include these “cryptic” floral traits, like the UV bulls-eye.…”
mentioning
confidence: 99%
“…Ultraviolet absorbing ''floral guides'' that are invisible to humans are perceptible to pollinators. Not only do they serve to orient bees at close range towards the source of reward, but they also affect visitation rates (Horth et al, 2014). The appearance of flowers revealed by UV photography is illustrated in Fig.…”
Section: Colour Perceptionmentioning
confidence: 99%